Hukum Lingkungan: Implementasi Peraturan Daerah tentang Pengelolaan Sampah Perkotaan di Kota Makassar - Arry Irawan; Patawari (Universitas Merdeka Madiun, 2023)
Abstract-This study aims to examine the urgency of applying environmental law in waste management and its impact on environmental protection, public health, and the achievement of sustainable development goals. This research method uses a qualitative approach. The data collection stage is done through interviews, observations, and document reviews. Observation of this research was carried out by direct observation at the location of the Final Disposal Site (TPA) in Makassar City and the surrounding urban environment. The document review is needed to collect data in the form of reports or information related to the implementation of local regulation number 4 of 2011 concerning Waste Management in Makassar City. The documents include regional regulation number 4 of 2011 concerning waste management in Makassar City, data on the amount of waste entering Antang Landfill, and evaluation data related to waste management in Makassar City. After the data has been collected, the process of processing and analyzing the research data is carried out. The data was analyzed by utilizing the Nvivo 12 Plus tool. The main finding of this research is that the application of environmental law in waste management is urgent because it is directly related to maintaining a clean and healthy environment, although the effort has been implemented, but it is still considered to need optimization. Environmental law plays a central role in regulating waste management practices that are safe, environmentally friendly, and in accordance with established standards. The main recommendations of this study are the need to strengthen the application of environmental law in waste management, increase public understanding of the importance of sustainable waste management practices, and promote green technology innovation in waste management to achieve sustainable development goals. Keywords-: Environmental law; regulation; local regulation; waste